Model Implementation of Quality Management System ISO 9001: 2008 Study on Motives, Benefits, Obstacles, and Success Factors - ., Adman; ., Rasto; Sarino, Alit; Yatimah, Durotul (International Journal of Engineering and Technology, 2018)
The problems are formulated as follows: ISO 9001: 2008 certification focuses more on proving compliance with standards and has not accommodated the needs of the education world to meet the expectations of stakeholders as well as continuous improvement of organizational performance. The need for implementation of Quality Management System in education sector becomes important. The focus of this research is to describe the condition of motives, benefits, obstacles and success factors of ISO 9001: 2008 Quality Management System. The research method used is explanatory survey method with descriptive analysis technique. The population of research states vocational school in Bandung and the sample is the manager of Quality Management System. The results describe the condition of motives, benefits, obstacles and success factors of implementation of ISO 9001: 2008 quality management. The motives categorical are high, high benefit, medium barriers and factors of high category success. This means that the impetus of the school to apply ISO is very good, the benefits of good ISO implementation and success factors in the application of ISO is very good, while in its application there are still barriers in the medium category.    Implementation of ISO 9001: 2008 quality management becomes a very important thing to improve the competitiveness of state vocational school in Bandung. A serious effort is required in implementing the ISO 9001: 2008 Quality Management system..